2011
DOI: 10.1002/jms.1983
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substituents and protonation on the mechanism of 1,3‐dipolar retro‐cycloaddition reaction of pyrrolidino[60]‐ and [70]fullerenes

Abstract: The mass spectra of new substituted pyrrolidino[60]- and [70]fullerenes have been obtained using electrospray ionization conditions in the positive and negative mode of detection with two different mass spectrometers, a quadrupole ion trap and a Fourier transform ion cyclotron resonance. Radical anions M(●-) and deprotonated molecules [M-H](-) are formed under negative electrospray ionization mass spectrometry conditions, and the collision-induced dissociations of both ionic species have been studied. Either n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 83 publications
2
14
0
Order By: Relevance
“…The corresponding protonated molecule [M+H] + ( 1b ) was observed at m/z 1013 and the mass spectrum obtained by CID reveals a main fragment 7 at m/z 926 (75%). The formation of this ion can be explained by assuming a loss of a methyliminoacetate molecule (C 3 H 5 NO 2 , 87 u) (Scheme ), similarly to the eliminations reported to explain the fragmentations of protonated fulleropyrrolidines . The elimination of the pyrrolidine ring does not take place and the loss of the imino derivative molecule produces the formation of 7 , while the isoxazoline ring remains attached to the C 60 core.…”
Section: Resultsmentioning
confidence: 65%
See 4 more Smart Citations
“…The corresponding protonated molecule [M+H] + ( 1b ) was observed at m/z 1013 and the mass spectrum obtained by CID reveals a main fragment 7 at m/z 926 (75%). The formation of this ion can be explained by assuming a loss of a methyliminoacetate molecule (C 3 H 5 NO 2 , 87 u) (Scheme ), similarly to the eliminations reported to explain the fragmentations of protonated fulleropyrrolidines . The elimination of the pyrrolidine ring does not take place and the loss of the imino derivative molecule produces the formation of 7 , while the isoxazoline ring remains attached to the C 60 core.…”
Section: Resultsmentioning
confidence: 65%
“…Despite these data, the reduced basicity seems to be enough to permit the protonation of the nitrogen atom resulting in the formation of the corresponding [M+H] + ion. We have previously reported that the protonated molecules [M+H] + of pyrrolidinofullerenes do not undergo the retro‐cycloaddition reaction under CID conditions . In this case, the protonation seems to avoid the loss of the corresponding azomethine ylide molecule.…”
Section: Methodsmentioning
confidence: 95%
See 3 more Smart Citations